A New Cage-Like Particle Adjuvant Enhances Protection of Foot-and-Mouth Disease Vaccine - Bidart, Juan; Kornuta, Claudia; Gammella, Mariela; Gnazzo, Victoria; Soria, Ivana; Langellotti, Cecilia; Mongini, Claudia; Galarza, Roxana; Calvinho, Luis; Lupi, Giuliana; Quattrocchi, Valeria; Marcipar, Ivan; et al. (Frontiers in Veterinary Science, 2020)
Foot-and-Mouth Disease (FMD) is an acute viral disease that causes important economy losses. Vaccines with new low-cost adjuvants that stimulate protective immune responses are needed and can be assayed in a mouse model to predict their effectiveness in cattle. Immunostimulant Particle Adjuvant (ISPA), also known as cage-like particle adjuvant, consisting of lipid boxes of dipalmitoyl-phosphatidylcholine, cholesterol, sterylamine, alpha-tocopherol, and QuilA saponin, was shown to enhance protection of a recombinant vaccine against Trypanosoma cruzi in a mouse model. Thus, in the present work, we studied the effects on the magnitude and type of immunity elicited in mice and cattle in response to a vaccine based on inactivated FMD virus (iFMDV) formulated with ISPA. It was demonstrated that iFMDV–ISPA induced protection in mice against challenge and elicited a specific antibody response in sera, characterized by a balanced Th1/Th2 profile. In cattle, the antibody titers reached corresponded to an expected percentage of protection (EPP) higher than 80%. EPP calculates the probability that livestock would be protected against a 10,000 bovine infectious doses challenge after vaccination. Moreover, in comparison with the non-adjuvanted iFMDV vaccine, iFMDV–ISPA elicited an increased specific T-cell response against the virus, including higher interferon gamma (IFNγ)+/CD8+ lymphocyte production in cattle. In this work, we report for first time that an inactivated FMDV serotype A vaccine adjuvanted with ISPA is capable of inducing protection against challenge in a murine model and of improving the specific immune responses against the virus in cattle.